The Lyrical Subject and the Lyrical Object In the Lyrics of P.Mirzabaeva - Aliyeva Khurliman Rakhmanbergenovna (International Journal on Integrated Education, 2023)
In the article, the problem of lyrical subject and lyrical object is studied on the example of contemporary P.Mirzabaeva's lyrics.